Relationship between infants with right cranial deformity and delay in the area of language - Josefa González Santos; Raquel De la De la Fuente Anuncibay; Jerónimo Javier González Bernal (INFAD, 2016)
The incidence of skull deformity in infants and its relation to some aspects of further development, is a matter of concern to professionals from different areas such as health, psychology, education and the family environment of the patient. To this end, an investigation was conducted with a sample of 38 infants who had cranial deformity from a 18-month longitudinal study carried out in primary care base Burgos Center. Brunet Lezine scale was used to assess the development in some areas. The results showed that those infants who had right cranial deformity, scored lower on the language area of the scale, those who had left cranial deformity. While some caution in the interpretation of results is needed, one could infer that the deformity, the backlash effect of the brain, do not allow the proper expansion of the area of language in these cases. The multidisciplinary treatment and monitoring could also be key to improving the prognosis.